Sufism in Historical Perspective: From Classical Traditions to Modern Interpretations - Hanesty Faradila; Aimmatuz Sa’adah; Cukup Rojali; Hajam Hajam (UIN Imam Bonjol Padang, 2024)
Sufism is a spiritual dimension of Islam that grew out of the early Islamic tradition of asceticism, where the companions and followers of the Prophet lived simply to draw closer to God. This research explores the historical development of Sufism from the 3rd to the 6th centuries of the Islamic calender, focusing such as Hasan al-Basri, Rabi’ah al-Adawiyah, Al-Junaid al-Baghdadi and Al-Ghazali played significant roles in shaping Sufism, emphasizing a balance between spirituality and Islamic law. From the 6th to the 11th centuries, Sufism became institutionalized through various Sufi orders like Qadiriyya and Naqshabandiyya, which spread Islam to regions like the Indonesian archipelago. These orders effectively combined Islamic teachings with local cultures. While some criticized Sufism for deviating from Islamic law, reformers like Shaykh Ahmad Sirhindi ensured its continued relevance. Today, Sufism offers spiritual solutions to modern challenges such as materialism and individualism, guiding Muslims toward a deeper connection with God. Sufi teachings not only purify the soul but also strengthen morality and promote social harmony.